The Role of Village-Owned Enterprises (BUMDes) in Empowering Village Communities Through the Village Livestock Program in Mahakam Regency - Yosep Lasah; Sri Kamariyah; Ika Devy Pramudiana (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This research is qualitative research with descriptive analysis, data collection techniques using interviews, observations, and documentation. The informants in the study included authorized officials consisting of the Head of the Community Empowerment and Village Government Office (DPMPD) of Mahakam Regency and the Head of the Food Security and Agriculture Service of Mahakam Regency. The data analysis technique uses Miles and Huberman interactive data analysis techniques. The results of the study show that BUMDES has an active role in Community Empowerment Through the Cattle Profit-Sharing Program in Mahakam Regency. This active role is carried out by providing facilities such as cow seeds, vitamins and cage making. The participatory role of BUMDES is carried out through awareness and socialization to the village community directly. The role of BUMDES in empowerment through the cattle profit-sharing program can increase income where those who used to only rely on as farm workers now with the cattle profit-sharing program managed by village-owned enterprises (BUMDes) can now raise their own cows. Obstacles to BUMDES in Community Empowerment Through the Profit-Sharing Program in Mahakam Regency include technical obstacles in maintenance, the existence of predators that attack livestock and fluctuations in the selling price of cattle. Another obstacle is the lack of knowledge of cattle farmers in the maintenance process, this is due to the lack of special training for cattle farmers.